Criminal conduct and substance abuse treatment for women in correctional settings: female-focused strategies for self-improvement and change pathways to responsible living - Milkman, Harvey B. (Adjunct provider's guide, 2008)
Women and crime -- Connecting female substance abuse cognition and crime -- Mental and physical health issues in female criminal justice clients -- Adolescent girls and delinquency: the route into correctional settings -- Understanding posttraumatic stress disorder -- Assessment with female judicial clients -- Gender as culture and other diversity considerations -- Gender specific strategies and models for treatment